Providing software support for economic analysis - Starkova, Olha; Bondarenko, Dmytro; Hrabovskyi, Yevhen (Technology audit and production reserves, 2023)
Today, modern software and hardware of information technologies are used to automate production processes, starting from modeling of technical developments and automated computer systems. This study is aimed at describing the process of implementing software support for economic analysis of the enterprise, which will calculate the main economic indicators and informatively display the calculated data. The object of the study is an automated system for calculating and maintaining the main economic indicators of the enterprise. The subject of research is methods of database design and development, data visualization and web applications. A review of literature sources allowed to conclude that most often to assess the economic performance of the enterprise, standard technologies are used, which the authors adapt to specific economic problems. In addition, the analysis of modern research has not identified a single software product that would collect, accumulate, analyze information and calculate the main indicators of economic activity of the enterprise, as well as monitor changes in such indicators in the dynamics. Automation of calculation of economic indicators, statistical analysis and visualization of data gives the chance to carry out effective management of the enterprise in modern economic conditions. The developed system allows to analyze the use of fixed assets; working capital analysis; analysis of the use of labor resources; profitability analysis; analysis of financial stability of enterprises. The paper shows the process of developing a functional model of a web application for the automated calculation of key economic indicators, and presents the advantages and disadvantages of working with the PostgreSQL database management system. The structure of the developed database, which consists of four tables, is given. An example of the work of the developed web application is presented.